Tinjauan Hukum mengenai Penyelesaian Sengketa Konsumen terhadap PT TIKI di BPSK WKP II Provinsi Banten (Studi Kasus: Putusan No. 175K/Pdt.Sus-BPSK/2021) - Neneng Adelia; Mohammad Hifni; Safiulloh Safiulloh (AHKAM, 2025)
The limited number of studies on consumer dispute resolution through the Consumer Dispute Settlement Agency (BPSK) underpins this research, despite its significant implications for consumer rights protection and legal certainty in Indonesia. This study aims to analyze the mechanism of consumer dispute resolution against PT Citra Van Titipan Kilat (TIKI) at BPSK WKP II, Banten Province, and to evaluate the effectiveness of BPSK decisions in enforcing business actors’ legal responsibility based on the principle of strict liability in civil law. A qualitative case study approach was employed, drawing on BPSK and Supreme Court rulings related to case No. 175K/Pdt.Sus-BPSK/2021, as well as interviews with BPSK members and affected consumers. Data were collected through official document analysis, semi-structured interviews, and participatory observation, then analyzed using thematic and comparative techniques. The findings reveal that PT TIKI was proven to have altered delivery services without consumer consent, causing material and immaterial losses, and that BPSK effectively applied arbitration as a fast, efficient, and low-cost dispute resolution mechanism. These findings support the theory of strict liability in civil law and affirm BPSK’s role as an effective quasi-judicial body in upholding consumer rights and ensuring legal certainty, although enforcement of decisions still requires supervision and clear limitations of authority. The implications include theoretical contributions to the literature on alternative dispute resolution (ADR) and strict liability of business actors, as well as practical contributions in the form of recommendations for BPSK, business actors, and policymakers to strengthen dispute resolution mechanisms and consumer protection.